Spatiotemporal variation and driving force of gully erosion in the Pisha sandstone area - Zhang, Yu; Li, Long; Liu, Linfu; Zhang, Shangxuan; Zhao, Wenzhuo; Ren, Yanan; Yang, Yue (Frontiers in Environmental Science, 2024)
The experiment was conducted on gully slopes with slopes ranging from 80° to 90° to investigate the relationship between erosion rates, spatial and temporal changes in microtopography, and drivers of erosion on gully slopes in different seasons. To precisely characterize the microtopography of slopes where debris slides occur, we used the RIEGL VZ-400 3D laser scanner to scan the observation site and acquire point cloud data on the slope’s microtopography. Using the “data conversion module” of ArcGIS software, the point cloud data were transformed into raster data. Through the “3D analysis,” “hydrological analysis,” and “grid calculator” modules, the basic microgeomorphological indicators were extracted from the gully slope grid data, and the erosion rate and microterrain evolution mechanism of the gully slope in different seasons were also determined. The results revealed the following: (1) in the Pisha sandstone area, erosion was relatively strong in the first quarter, with 65% of the area being eroded. The average erosion rates over the four quarters followed the order of first quarter > fourth quarter > second quarter > third quarter, from fastest to slowest. (2) As the soil on the gully slope thawed, melt water increased soil moisture. This phenomenon sharply increased surface roughness in the first quarter. The correlation coefficients between the erosion rate and temperature in the first and fourth quarters were 0.75 and 0.82, respectively. Temperature mainly affected the erosion rate through surface roughness. The direct path coefficient of this effect was 0.72. (3) In the first and fourth quarters, temperature and wind speed were the main factors influencing the erosion rate; the relationship between surface roughness and other factors was evident, making surface roughness the best topographic factor for assessing slope erosion in the Pisha sandstone area. The results of this study aim to provide theoretical references for understanding the gravity erosion mechanism of gully slopes in the Pisha sandstone area and contribute to the high-quality development of the Yellow River Basin.